TRIPLE BOTTOM LINE ACCOUNTING PATTERN AND PROFITABILITY OF FIRMS: AN EMPIRICAL STUDY OF OIL AND GAS COMPANIES IN NIGERIA - Michael, Ekwe C.; Isaac, Odogu Laime; Adaure, Mebrim Angelina (International Journal For Research In Business, Management And Accounting, 2021)
This research paper examines the important of triple bottom line accounting pattern on the profitability of firms in Nigeria. To achieve the above objective, companies with good evidence of social and environmental cost record were sorted from the oil and gas industry in Nigeria. Hypotheses were formulated, and a review of related literature was made. Theory in support of sustainability was analyzed, Data were collected from oil and gas annual reports and financial statement of Conoil and Forte Oil Nigeria Plc, The data were presented and analyzed, while the formulated hypotheses were tested using the Ordinary Least Square (OLS), Our findings indicated that the implementation of triple bottom line accounting pattern in organizations would enable them report profitability accurately to stakeholders, measurement and allocation of environmental and social costs pertaining to the activities of the organization. Based on this, it was recommended that firms should implement triple bottom line accounting patterns to enable them identify, measure and allocate environmental and social costs; and also, provide managers with strategies and techniques for managing performance across the three dimensions.